O ADULTOCENTRISMO E AS POLÍTICAS PÚBLICAS DESTINADAS ÀS INFÂNCIAS NO BRASIL: PISTAS PARA UM CRIANÇAR COM TRABALHADORAS - Fim, Matheus Magno dos Santos (2022)
The present dissertation proposes to qualify the idea of adult-centric practices, analyzing how these practices cross and constitute public policies aimed at childhood in Brazil. The research is constituted with the tool-concepts of Institutional Analysis